Bistatic sonars: sea trials, laboratory experiments and future surveys - BLONDEL, Philippe; PACE, Nick G. (Archives of Acoustics, 2009)
Bistatic sonars use separate transmitter and receiver(s), optimising the information received from seabed/target(s) scattering. Laboratory experiments are ideal to understand scattering processes and to optimise data collection strategies. They can be full-scale or scaled down. In the latter case, the influence on bistatic scattering processes needs to be carefully weighed, to validate the transition to full-scale experiments. This is particularly relevant as sea trials are expensive, difficult to conduct, and generally impossible to repeat. This article presents the results from: (1) scaled experiments on bare seabed and targets, performed at Bath and other places; (2) full-scale experiments in the GESMA submarine pens during the EC-SITAR project and (3) sea trials from similar experiments in Italy and Sweden. These results are put into the wider context of other international efforts. These three approaches (scaled and full-scale experiments plus sea trials) can be used in synergy. This has important implications for future experiments, the design of surveys and instruments, and analyses of past/future acoustic datasets.